2008
DOI: 10.1002/gps.2143
|View full text |Cite
|
Sign up to set email alerts
|

Use of benzodiazepines, depressive symptoms and cognitive function in old age

Abstract: In old age the use of benzodiazepines is associated with depressive symptoms and the use of benzodiazepines may precede the development of depressive symptoms. Treating physicians seem to be aware of the detrimental effects of benzodiazepines on cognitive function. However, they should be cautious in prescribing a new benzodiazepine in old age and monitor elderly benzodiazepine users for development of depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 34 publications
0
36
0
1
Order By: Relevance
“…This chronic concomitant use of psychotropic drugs to treat depression is not appropriate in the geriatric population who has already an increased risk of interactions and adverse drug reactions. On the one hand, it is not surprising we found an association between depression and BZD/Z use, because depression can be the reason of initiating a BZD/Z drug, definitely when depression is related to a disturbed sleep pattern and anxiety [38]. On the other hand, a study in 2007 revealed that the use of hypnotics was associated with an increased incidence of depression, suggesting hypnotics may be contra indicated when there is a risk for depression [39].…”
Section: Insomniamentioning
confidence: 87%
“…This chronic concomitant use of psychotropic drugs to treat depression is not appropriate in the geriatric population who has already an increased risk of interactions and adverse drug reactions. On the one hand, it is not surprising we found an association between depression and BZD/Z use, because depression can be the reason of initiating a BZD/Z drug, definitely when depression is related to a disturbed sleep pattern and anxiety [38]. On the other hand, a study in 2007 revealed that the use of hypnotics was associated with an increased incidence of depression, suggesting hypnotics may be contra indicated when there is a risk for depression [39].…”
Section: Insomniamentioning
confidence: 87%
“…45 Long-term sedative/anxiolytic drug use has been associated with an increased risk of depression. 46 In turn, depres-…”
Section: Main Findingsmentioning
confidence: 99%
“…3 BDZs have been associated with cognitive impairment, depressive symptoms, poor physical function, falls, and fractures. [4][5][6][7] The responsible prescribing of BDZs in psychiatric disorders has recently been debated. 8 Research into the association between BDZ use and mortality has been inconsistent.…”
mentioning
confidence: 99%